The aggressivness of Diaporthe longicolla and Diaporthe pseudolongicolla isolates tested by the soybean seed's artificial inoculation - Duvnjak, Tomislav (Array, 2021)
This study"s objective was to determine if there was a difference in aggressiveness between the Diaporthe longicolla and the Diaporthe pseudolongicolla isolates infecting the soybean seeds. An artificial inoculation was performed under laboratory conditions and in a greenhouse on a soybean cultivar (Tisa) created in the breeding program of the Agricultural Institute Osijek and represented in a large-scale production in the Republic of Croatia. An attempt was made to discover whether the isolates of the recently described D. pseudolongicolla were more aggressive to the soybean seeds than the D. longicolla isolates, which have manifested a high aggressiveness to the soybean seeds throughout a series of earlier experiments. The D. pseudolongicolla isolates used in the experiment were isolated from the infected seeds pertaining to a wide production in the vicinity of Osijek.